Taking teaching and learning seriously: Approaching wicked consciousness through collaboration and partnership - Adam H. Smith; Barbara J. Rodriguez; Janel Seeley; John C. Foo; Laurel L. Hester; Laurie L. McCarty; Linda M. Boland; Lindsay Doukopoulos (To Improve the Academy, 2022)
The ongoing COVID-19 pandemic has demanded large-scale collaboration within all organizations, including higher education, and taking teaching and learning seriously, in this moment, means leveraging partnerships to address the wicked (large, complex) problems cited by Bass (2020). These problems are not ours alone to solve; rather, we make the case for a “wicked consciousness,” an amalgam of perspectives, in educational development. Guided by intellectual humility, our success as educational developers ought to be measured by the quality of our collaborations as well as our ability to learn with others, form equitable partnerships, and lead others by our example.